A prophylactic effect of aluminium-based adjuvants against respiratory viruses via priming local innate immunity. Issue 1 (31st December 2022) - Wang, Xin; Yin, Xiaochen; Zhang, Boya; Liu, Chenfeng; Lin, Yahua; Huang, Xiaofen; Li, Yufang; Shen, Chenguang; Zheng, Weibin; Fu, Guofeng; Chen, Junyu; Wen, Yanling; et al.
ABSTRACT: Infection caused by respiratory viruses can lead to a severe respiratory disease and even death. Vaccination is the most effective way to prevent the disease, but it cannot be quickly applied when facing an emerging infectious disease. Here, we demonstrated that immunization with an aluminium-zinc hybrid particulate adjuvant (FH-001) alone, bearing great resemblance in morphology with commonly used aluminium-based adjuvants in vaccines, could quickly induce mice to generate a broadly protective immune response to resist the lethal challenge of influenza B viruses. Furthermore, a multi-omics-based analysis revealed that the alveolar macrophage and type I interferon pathway, rather than adaptive immunity and type II interferon pathway, were essential for the observed prophylactic effect of FH-001. More importantly, a similar protective effect was observed against influenza A virus strain A/Shanghai/02/2013(H7N9), A/California/04/2009(H1N1) and respiratory syncytial virus. Therefore, we introduced here a new and promising strategy that can be quickly applied during the outbreak of emerging respiratory viruses.